Serious Cardiovascular Adverse Events Reported with Intravenous Sedatives: A Retrospective Analysis of the MedWatch Adverse Event Reporting System - Matthew S. Duprey; Nada S. Al-Qadheeb; Nick O'Donnell; Keith B. Hoffman; Jonathan Weinstock; Christopher Madias; Mo Dimbil; John W. Devlin (Adis, Springer Healthcare, 2019)
Abstract Background Serious cardiovascular adverse events (SCAEs) associated with intravenous sedatives remain poorly characterized. Objective The objective of this study was to compare SCAE incidence, types, and mortality between intravenous benzodiazepines (i.e., diazepam, lorazepam, and midazolam), dexmedetomidine, and propofol in the USA over 8 years regardless of the clinical setting where it was administered. Methods The Food and Drug Administration's MedWatch Adverse Event Reporting System was searched between 2004 and 2011 using the Evidex® platform from Advera Health Analytics, Inc. to identify all reports that included one or more of ten different SCAEs (package insert incidence ≥ 1%) and where an intravenous benzodiazepine, dexmedetomidine, or propofol was the primary suspected drug. Results Among the 2326 Food and Drug Administration's MedWatch Adverse Event Reporting System cases reported, 394 (16.9%) were related to a SCAE. The presence of a SCAE (vs. a non-SCAE) is associated with higher mortality (34 vs. 8%, p < 0.001). The percentage of cases with one or more SCAE, the case mortality rate (%), and the incidence of each SCAE (per 106 days of sedative exposure), respectively, were benzodiazepines (14, 26, 13) [diazepam (13, 23, 31); lorazepam (15, 43, 14); midazolam (14, 20, 11)]; dexmedetomidine (40, 15, 13); and propofol (17, 39, 7). Propofol (vs. either a benzodiazepine or dexmedetomidine) was associated with more total SCAEs (268 vs. 126, p < 0.001) but a lower incidence (per 106 days of sedative exposure) of SCAE (7 vs. 13, p = 0.0001) and cardiac arrest [6.3 (benzodiazepine) vs. 6.7 (dexmedetomidine) vs. 1.4 (propofol), p < 0.0001]. Conclusions Serious cardiac adverse events account for nearly one-fifth of intravenous sedative Food and Drug Administration's MedWatch Adverse Event Reporting System reports. These SCAEs appear to be associated with greater mortality than non-cardiac serious adverse events. Serious cardiac events may be more prevalent with either benzodiazepines or dexmedetomidine than propofol.